A combined experimental and theoretical approach to investigate the structure, magnetic properties and DNA binding affinity of a homodinuclear Cu(ii) complex. (30th April 2019) - Ahamad, M. Naqi; Shahid, M.; Ansari, Azaj; Kumar, Manjeet; Khan, Ishaat M.; Ahmad, Musheer; Rahisuddin,; Arif, Rizwan
Abstract : A dicopper(ii ) complex of a flexible amino alcohol anchored with an acetate auxiliary was designed and characterized by spectral, X-ray crystallographic, magnetic and DFT studies; moreover, it was evaluated for its DNA binding properties. The experimental results are supported by theoretical analyses. Abstract : Herein, an antiferromagnetic homodinuclear Cu(ii ) complex of propanolamine, [Cu2 (pa)2 (OAc)2 ] (1 ), containing an acetate auxiliary was crystallized out. The complex was characterized by spectral, X-ray crystallographic, magnetic and DFT/TD-DFT studies. Single crystal X-ray data reveal that 1 crystallizes in the triclinic system with the P 1̄ space group, and each Cu(ii ) ion adopts a four-coordinated square planar geometry with the [N, O, O, O] donor set. The two [Cu(CH3 COO)(pa)] + units are connected through two alkoxy groups of the pa − ligand belonging to each unit; this results in the formation of a binuclear Cu(ii ) system with the bridging Cu1–O1–Cu2 angle = 103.81° and the intradimer Cu⋯Cu distance = 3.022 Å. The experimental results obtained via the binding experiments of the present complex with DNA are in line with the theoretical results. The auxiliary acetate group and the bridged pa − ligand facilitate the binding tendency of the complex to DNA in the minor groove region (as confirmed by docking analysis), thereby forming stronger H-bonding interactions. The easy transfer of an electron from the HOMO of DNA to the LUMO of the complex further supports the existence of a stronger binding interaction, as confirmed by the DFT analysis. Temperature variable magnetic studies (SQUID measurements) revealed the presence of strong antiferromagnetic interactions ( J = −222.4(2) cm −1 ) between two Cu(ii ) nuclei in a molecule, and the presence of these interactions was further supported by theoretical studies. The larger Cu⋯Cu distance and Cu–O–Cu angle are the factors behind the antiferromagnetic exchange between two Cu(ii ) centers. Thus, the present study establishes that the fine tuning of structures in transition metal complexes can result in the formation of magnetically and biologically important molecules for future applications.